(untitled) (Web of Teachers: Inderscience Research, 2024)
This study delves into the intricate web of linguistic evolution by examining the Latin and Greek derivational potential embedded within English word formation. Through a comprehensive analysis, we unveil the rich heritage and cross-cultural influences that have shaped the lexicon of the English language. Employing a multidisciplinary approach, this research amalgamates linguistics, cultural studies, and etymology to unravel the intricate tapestry of English vocabulary construction. The findings shed light on the dynamic interplay between linguistic roots and cultural contexts, illuminating the pathways through which words transcend boundaries and bridge diverse cultural landscapes.